Evaluación de la calidad del aire intramural en aulas de la fundación Universidad de América (2024)
This thesis evaluates the indoor air quality (IAQ) in the classrooms of the Fundación Universidad de América, focusing on carbon dioxide (CO2) levels as a key indicator. The main objective of the research is to propose the implementation of a monitoring and control system for CO2 levels in classrooms of the Fundación Universidad de América to improve the air quality in these educational spaces. Through a technical diagnosis and a monitoring campaign in three classrooms of the university, CO2 concentrations were analyzed based on capacity and ventilation conditions. The results reveal that most of the data obtained exceed the recommended limits, which underlines the need to implement a system that improves the ventilation of these indoor spaces. Although the effects on health were not directly investigated, the data obtained suggest that constant monitoring of air quality is essential. It is concluded that the implementation of a continuous monitoring system that allows regulating CO2 levels in real time is necessary to guarantee a healthier indoor environment that is suitable for learning processes. This approach allows the environmental engineer to apply his technical knowledge to evaluate the accuracy of measurement equipment and formulate effective solutions to improve air quality.